PSYCHIATRIC SEQUELAE OF AMPUTATION : II LONG TERM EFFECTS - Trivedi, J.K. (Medknow Publications, 1997)
Psychiatric sequelae present after 6 months to 2 years following amputation were studied in a group of 25 subjects. The subjects were screened on SCID, HRSD and HARS. The most common diagnoses were depressive disorder NOS (20.6%) and major depressive disorder (10.3%). Patients having right sided amputation were more psychiatrically ill than those with loss of a left limb. Phantom limb was seen in about two-thirds of the total sample-more in the sick group (about 88%) than in the non-sick group (about 55%). Pain in the phantom limb was seen more in the sick group, but telescopy and movement were more frequently complained of by subjects of the non-sick group.